Nanoparticle‐Laden Macrophages for Tumor‐Tropic Drug Delivery. Issue 50 (11th October 2018) - Zhang, Weizhong; Wang, Mengzhe; Tang, Wei; Wen, Ru; Zhou, Shiyi; Lee, Chaebin; Wang, Hui; Jiang, Wen; Delahunty, Ian Michael; Zhen, Zipeng; Chen, Hongmin; Chapman, Matthew; et al.
Abstract: Macrophages hold great potential in cancer drug delivery because they can sense chemotactic cues and home to tumors with high efficiency. However, it remains a challenge to load large amounts of therapeutics into macrophages without compromising cell functions. This study reports a silica‐based drug nanocapsule approach to solve this issue. The nanocapsule consists of a drug–silica complex filling and a solid silica sheath, and it is designed to minimally release drug molecules in the early hours of cell entry. While taken up by macrophages at high rates, the nanocapsules minimally affect cell migration in the first 6–12 h, buying time for macrophages to home to tumors and release drugs in situ. In particular, it is shown that doxorubicin (Dox) as a representative drug can be loaded into macrophages up to 16.6 pg per cell using this approach. When tested in a U87MG xenograft model, intravenously (i.v.) injected Dox‐laden macrophages show comparable tumor accumulation as untreated macrophages. Therapy leads to efficient tumor growth suppression, while causing little systematic toxicity. This study suggests a new cell platform for selective drug delivery, which can be readily extended to the treatment of other types of diseases. Abstract : Macrophages are exploited as a vehicle to deliver therapeutics to tumors . This is achieved by a silica‐based nanocapsule that can be engulfed by macrophages by large quantities but minimally release its payloads in the early hours of cell entry. This property buys time for macrophages to migrate to tumors to selectively kill cancer cells while causing minimal systemic toxicity.